Research of High-Temperature Heat and Mass Transfer and Kinetics of Phase Transformations during combustion higher alkanes in the air - Orlovska, S.G.; Odnostalko, A.O.; Karimova, F.F.; Shkoropado, M.S. (Physics and Chemistry of Solid State, 2015)
The paper presents a study of high-temperature heat and mass transfer and combustion kinetics of octadecane particle in room temperature air taking in consideration fuel heating, melting and evaporation. The consecutive stages of droplet combustion are described. Burning rate constants and flame heights are determined for droplets with different initial diameters